DEVELOPMENT AND EVALUATION OF AN ALTERNATIVE OBESE RAT ANIMAL MODEL OF TYPE 2 DIABETES - Islam , Shahidul; Mansoor, Shazia (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES The aim of this study was to develop and evaluate of an alternative obese rat model for type 2 diabetes. METHODOLOGY Forty, 6-week-old, male Wistar rats were randomly divided into 5 groups as: Normal Control (NC), Diabetic Control (DC), Saccharin low 0.033% (SACL), Saccharin medium 0.067% (SACM) and Saccharin high 1.33% (SACH). The DC group was only given 10% fructose in water while the SACL, SACM and SACH groups were supplied with 0.03%, 0.067% and 0.13% saccharin respectively, in combination with 10% fructose in drinking water for 4 weeks only, while the animals in NC group were fed with normal drinking water. Thereafter, all animals were given normal drinking water for the remaining period of the study and fed with commercially available rat chow diet ad libitum for the duration of the study. The Body Mass Index (BMI) of the animals were measured weekly, with a BMI ≥0.69 g/cm2 considered obese. Once obesity was confirmed, all rats in DC and SAC groups were injected intraperitoneally with a low dose (40 mg/kg BW) of streptozotocin (STZ) dissolved in 0.1 M citrate buffer (pH 4.5), while the animals in NC group were injected with an equivalent volume of citrate buffer. One week after the STZ injection, animals with a non-fasting blood glucose level ≥200 mg/dl were considered diabetic. RESULTS After the 13-week experimental period, the SACL group demonstrated a sustainably higher BMI and obesity level, higher blood glucose level as well as better anti-diabetic drug sensitivity, more insulin resistance, lower glucose tolerance and partial pancreatic β-cell damage in comparison to the other diabetic groups. CONCLUSION Considering all above, the 10% fructose along with 0.033% saccharin fed and STZ (40 mg/kg BW) injected group could be a suitable animal model of obesity-related type 2 diabetes.